2012
DOI: 10.1093/toxsci/kfs227
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maternal Exposure to Bisphenol A on Allergic Lung Inflammation into Adulthood

Abstract: Bisphenol A (BPA) is a high-production volume chemical classified as an environmental estrogen and used primarily in the plastics industry. BPA's increased usage correlates with rising BPA levels in people and a corresponding increase in the incidence of asthma. Due to limited studies, the contribution of maternal BPA exposure to allergic asthma pathogenesis is unclear. Using two established mouse models of allergic asthma, we examined whether developmental exposure to BPA alters hallmarks of allergic lung in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 51 publications
7
76
2
Order By: Relevance
“…In the present study, gestational and lactational exposure to low-dose BPA was found to induce persistent and more prominent changes in female offspring mice in terms of Th17 cell frequency, IL-17, IL-21, and RORγt mRNA expression. These gender-specific effects are consistent with previous studies showing that perinatal BPA exposure induces inflammation, alterations in energy expenditure, body composition and hormone levels, as well as behavioral changes (Bauer et al, 2012;Anderson et al, 2013;Kundakovic et al, 2013). Differential tissue distribution of BPA in male and female offspring mice may play a critical role in gender dimorphic phenotypes (Doerge et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, gestational and lactational exposure to low-dose BPA was found to induce persistent and more prominent changes in female offspring mice in terms of Th17 cell frequency, IL-17, IL-21, and RORγt mRNA expression. These gender-specific effects are consistent with previous studies showing that perinatal BPA exposure induces inflammation, alterations in energy expenditure, body composition and hormone levels, as well as behavioral changes (Bauer et al, 2012;Anderson et al, 2013;Kundakovic et al, 2013). Differential tissue distribution of BPA in male and female offspring mice may play a critical role in gender dimorphic phenotypes (Doerge et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In humans, prenatal and postnatal environmental BPA exposure is associated with various autoimmune diseases and inflammation during childhood and adulthood, including allergy, asthma and obesity (Spanier et al, 2012;Trasande et al, 2012;Mikołajewska et al, 2015). In animals, early-life exposure to BPA may produce considerable adverse effects to the immune system, such as cytokine secretion changes, immune-associated gene expression, T helper (Th)1/Th2 cell shifts, decrease in regulatory T cell (Treg) number, immune response abnormality, and allergic inflammation in offspring mice during the life course (Yoshino et al, 2004;Yan et al, 2008;Midoro-Horiuti et al, 2010;Bauer et al, 2012). However, the molecular mechanisms for immune disorders of BPA following perinatal exposure remain to be elucidated (Rogers et al, 2013), in particular the autoimmune-specific pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[141][142][143][144][145] These studies typically show effects of BPA on some aspects of immune response, but not all (i.e., altered innate but not adaptive immune responses, effects in some organs but not others, etc.). Because these studies used different agents to invoke immune responses and assessed different organs' responses, there is not yet enough evidence to determine whether the effects of BPA on the immune system are consistent.…”
Section: -53mentioning
confidence: 99%
“…155 Importantly, many significant effects are observed following administration of doses below the EPA reference dose of 50 μg/ kg body weight/day, and some of these studies show effects in the range of estimated human exposures (≤ 5 μg/kg body weight/ day). 118,124,126,130,132,133,135,136,141,143,150,152, Previous reviews have also noted a relatively large number of studies that demonstrated effects in the range of human exposures from dietary sources. 6,9 Studying actual or suspected human exposure levels in rodents may not be appropriate for risk assessment purposes as this leaves no margin of error for differences in metabolism between species or individuals, the presence of vulnerable human subpopulations, or the possibility that animal models are less sensitive than humans.…”
Section: -53mentioning
confidence: 99%
“…However, recent studies describe the nonmonotonic dose response relationship of BPA. Perinatal exposure to lower dose of BPA than LOAEL has been reported the harmful effects on endocrine system including reproductive system [4][5][6][7], immune system [8][9][10], pituitary gland [11][12][13][14][15][16][17][18][19][20], and metabolic system [21][22][23][24]. Because, the fetus and neonates are extremely sensitive to perturbation by hormone like chemicals, early life exposure to low dose BPA probably is able to affect the epigenetic mechanism.…”
Section: Introductionmentioning
confidence: 99%